Having a Finger in the Pie: Labor Power and Corporate Payout Policy. Issue 4 (6th April 2018) - Haw, In‐Mu; Hu, Bingbing; Wu, Donghui; Zhang, Xu
Abstract: Exploiting time‐series data on labor laws from 39 countries, we investigate how labor power influences firms' payouts. We find that legislative changes that strengthen labor power reduce firms' dividend payments and total payouts. The payout restriction effect of labor power is more pronounced in firms with greater labor intensity and in firms operating in countries with broader collective bargaining coverage and more effective law enforcement. Tightened operating flexibility and excess wage extraction are two plausible channels through which labor power affects payouts. These findings indicate that labor power is another important country‐wide institution that shapes corporate payout policy.